Astragalus Polysaccharide Suppresses Doxorubicin-Induced Cardiotoxicity by Regulating the PI3k/Akt and p38MAPK Pathways. (16th October 2014) - Cao, Yuan; Ruan, Yang; Shen, Tao; Huang, Xiuqing; Li, Meng; Yu, Weiwei; Zhu, Yuping; Man, Yong; Wang, Shu; Li, Jian
Abstract : Background . Doxorubicin, a potent chemotherapeutic agent, is associated with acute and chronic cardiotoxicity, which is cumulatively dose-dependent. Astragalus polysaccharide (APS), the extract of Astragalus membranaceus with strong antitumor and antiglomerulonephritis activity, can effectively alleviate inflammation. However, whether APS could ameliorate chemotherapy-induced cardiotoxicity is not understood. Here, we investigated the protective effects of APS on doxorubicin-induced cardiotoxicity and elucidated the underlying mechanisms of the protective effects of APS. Methods . We analyzed myocardial injury in cancer patients who underwent doxorubicin chemotherapy and generated a doxorubicin-induced neonatal rat cardiomyocyte injury model and a mouse heart failure model. Echocardiography, reactive oxygen species (ROS) production, TUNEL, DNA laddering, and Western blotting were performed to observe cell survival, oxidative stress, and inflammatory signal pathways in cardiomyocytes. Results . Treatment of patients with the chemotherapeutic drug doxorubicin led to heart dysfunction. Doxorubicin reduced cardiomyocyte viability and induced C57BL/6J mouse heart failure with concurrent elevated ROS generation and apoptosis, which, however, was attenuated by APS treatment. In addition, there was profound inhibition of p38MAPK and activation of Akt after APS treatment. Conclusions . These results demonstrate that APS could suppress oxidative stress and apoptosis, ameliorating doxorubicin-mediated cardiotoxicity by regulating the PI3k/Akt and p38MAPK pathways.